Antimelanogenic Effects of Raphanus sativus L. var. niger Roots on α‐MSH Stimulated B16F10 Melanoma Cells. (9th October 2018) - Ko, Ha Na; Kim, Jung Eun; Jo, Yeon Jeong; Hong, Seung Hyun; Yang, Da Wun; Kim, Gi Ok; Lee, Nam Ho
Abstract : This study was conducted to identify the antimelanogenic components from Raphanus sativus L. var. niger (black radish). Phytochemical study with the ethanol extract of black radish roots resulted in the isolation of six compounds: 3‐( E )‐(methylthio)methylene‐2‐pyrrolidinethione (1 ), ascorbigen (2 ), β‐sitosterol (3 ), palmitic acid (4 ), α‐linolenic acid (5 ), and 1‐linoleonyl glycerol (6 ). Among the isolates, the thione1 efficiently inhibited melanin synthesis in a concentration‐dependent manner in α‐MSH stimulated B16F10 melanoma cells. Western blotting analysis for the key melanogenic enzymes showed that compound1 decreased tyrosinase and tyrosinase‐related protein‐2 expressions. These results demonstrated that the black radish extract including pyrrolidinethione1 could be useful as antimelanogenic agents in cosmetic or pharmaceutical applications. Abstract : Phytochemical studies of ethanol extract from black radish ( Raphanus sativus L. var. niger ) roots led to isolation of six compounds including 3‐( E )‐(methylthio)methylene‐2‐pyrrolidinethione (1 ) (a). Compound1 reduced melanin production in a dose‐dependent manner in α‐MSH stimulated B16F10 melanoma cells (b). Also, the cellular tyrosinase activity was downregulated by compound1 (c).